2016
DOI: 10.1002/2016gc006456
|View full text |Cite
|
Sign up to set email alerts
|

Sediment melting during subduction initiation: Geochronological and geochemical evidence from the Darutso high‐Mg andesites within ophiolite melange, central Tibet

Abstract: In addition to fluids, the concept of sediment‐derived melts infiltrating the fore‐arc mantle during subduction initiation has been proposed based on studies of modern subduction zones and ophiolite mélange. However, outcrops that contain the products of such melts are rare, especially in conjunction with boninite. New U‐Pb zircon dating reveals that the Darutso volcanic rocks (DVRs) within ophiolitic mélange in the Beila area, central Tibet, crystallized at ∼164–162 Ma. This is the first recognition of Jurass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 109 publications
(217 reference statements)
3
71
0
Order By: Relevance
“…The Elitu samples are high‐Mg andesites. For the high‐Mg andesitic magmas, three different petrogenetic origins have been proposed, involving (a) the delaminating eclogitic crust (Tatsumi, ; Yang et al, ; Zeng, Chen, Xu, Wang, & Huang, ), (b) a young and hot slab (Li et al, ; Suzuki & Tatsumi, ) or (c) slab‐derived fluid/melt metasomatised source (Ma et al, ; Suzuki & Tatsumi, ; Zeng et al, ).…”
Section: Petrogenesis Of the Early Permian Igneous Rocksmentioning
confidence: 99%
See 3 more Smart Citations
“…The Elitu samples are high‐Mg andesites. For the high‐Mg andesitic magmas, three different petrogenetic origins have been proposed, involving (a) the delaminating eclogitic crust (Tatsumi, ; Yang et al, ; Zeng, Chen, Xu, Wang, & Huang, ), (b) a young and hot slab (Li et al, ; Suzuki & Tatsumi, ) or (c) slab‐derived fluid/melt metasomatised source (Ma et al, ; Suzuki & Tatsumi, ; Zeng et al, ).…”
Section: Petrogenesis Of the Early Permian Igneous Rocksmentioning
confidence: 99%
“…Some Cenozoic high‐Mg andesites are formed by partial melting of delaminating eclogitic crust in continental rifting or extension settings (Tatsumi, 2006; Yang et al, 2015; Zeng et al, ). These rocks often show high SiO 2 contents and enriched zircon Lu‐Hf compositions.…”
Section: Petrogenesis Of the Early Permian Igneous Rocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Compositions of the Dunzhugur dikes reported by [Sklyarov et al, 2016] are shown. Dunzhugur dikes [Sklyarov et al, 2016] La/Yb (PM) εNd ported in Oman ophiolite [Haase et al, 2015] and some Tibetian ophiolites [Zeng et al, 2016]. The studied Eastern Sayan ophiolites might record similar case of sediment melt participation in ophiolite petrogenesis.…”
Section: Geodynamics and Tectonophysics P U B L I S H E D B Y T H E I Nmentioning
confidence: 99%